IMPLEMENTASI ALGORITMA APRIORI TID UNTUK MENGETAHUI POLA PENJUALAN KERAMIK - Anri Muda Siregar; Muhammad Syahrizal (STMIK Budi Darma, 2019)
At PT. JUI SHIN INDONESIA Medan Deli is checking the sales of ceramics once a year. The amount of ceramics needed at PT. JUI SHIN INDONESIA Medan Deli is so big. The lack of good sales interactions has resulted in ceramics sales and the quality of service to the council going down. This research expects to analyze the general operating picture, ceramic sales of PT. JUI SHIN INDONESIA Medan Deli. The problem often faced is that goods are not neatly arranged and cannot be utilized for system development and are only used as archives at PT. JUI SHIN INDONESIA Medan Deli. To find out the pattern of ceramics sales, ceramics sales have so far been ineffective because the data stored in Microsoft Excel is still not good so it requires a long time if at any time the warehouse of PT. JUI SHIN INDONESIA Medan Deli and other company administrations do data checking. For that we need a system that can facilitate the warehouse in analyzing the sales data of ceramics. This algorithm is one part of association rule mining. This method aims to obtain the rules of association or relations between groups of items. by using the Tanagra tool application method for testing data on ceramic sales transactions.Keywords: To Know the Pattern of Ceramic Sales Using the Aryri TID Algorithm